Plant Golgi ultrastructure - Robinson, David G. (Journal of microscopy, 2020)
The plant Golgi apparatus (sensu lato: Golgi stack + Trans Golgi Network, TGN) is a highly polar and mobile key organelle lying at the junction of the secretory and endocytic pathways. Unlike its counterpart in animal cells it does not disassemble during mitosis. It modifies glycoproteins sent to it from the endoplasmic reticulum (ER), it recycles ER resident proteins, it sorts proteins destined for the vacuole from secretory proteins, it receives proteins internalised from the plasma membrane and either recycles them to the plasma membrane or retargets them to the vacuole for degradation. In functional terms the Golgi apparatus can be likened to a car factory, with incoming (COPII traffic) and returning (COPI traffic) railway lines at the entry gate, and a distribution centre (the TGN) at the exit gate of the assembly hall. In the assembly hall we have a conveyor belt system where the incoming car parts are initially assembled (in the cis-area) then gradually modified into different models (processing of secretory cargo) as the cars pass along the production line (cisternal maturation). After being released the trans-area, the cars (secretory cargos) are moved out of the assembly hall and passed on to the distribution centre (TGN), where the various models are placed onto different trains (cargo sorting into carrier vesicles) for transport to the car dealers. Cars with motor problems are returned to the factory for repairs (endocytosis to the TGN). This simple analogy also incorporates features of quality control at the COPII entry gate with defective parts being returned to the manufacturing center (the ER) via the COPI trains (vesicles). In recent years, numerous studies have contributed to our knowledge on Golgi function and structure in both animals, yeast and plants. This review, rather than giving a balanced account of the structure as well as of the function of the Golgi apparatus has purposely a marked slant towards plant Golgi ultrastructure integrating findings from the mammalian/animal field.